Peningkatan Hasil Belajar Murid Melalui Metode Tanya Jawab pada Mata Pelajaran Ilmu Pengetahuan Sosial Di Kelas IV SD Inpres 5/81 Pattiro Sompe Kabupaten Bone - Hajja Nursiah (Universitas Negeri Makassar, 2022)
The problem in this research is to find out the description of improving student learning outcomes through the question and answer method in social science subjects (IPS) in class IV SD Inpres 5/81 Pattiro Sompe, Bone Regency. This research is a descriptive study with the focus of the research being the 10th grade students of SD Inpres 5/81 Pattiro Sompe, Bone Regency. Data collection with observation, test, and documentation techniques, while data collection with observation techniques to collect data on data analysis activities used is descriptive statistical analysis in the form of percentages and frequency tables. The results obtained by Class IV students of SD Inpres 5/81 Pattiro Sompe, Bone Regency, in general, experienced an increase in learning outcomes in Social Sciences (IPS) through questions and answers by paying attention to aspects, namely: (a) increasing learning outcomes in Social Sciences (IPS), (b) able to ask questions to the teacher or other students. Meanwhile, the efforts taken by teachers in the field of Social Sciences (IPS) in improving the learning outcomes of fourth grade students, namely (a) training students to dare to ask questions, (b) training students to answer.